INTEGRATING MULTI-FACTOR AUTHENTICATION IN A STUDENT RIDE-SHARING SYSTEM FOR IMPROVED SECURITY - Michael Lancaster; Ethan Leschen (Academic Reseach Library for International Journal of Computer Science & Information System, 2025)
This article proposes a Student Ride-Sharing System that integrates Multi-Factor Authentication (MFA) to ensure secure and reliable transportation for students. With the increasing demand for safe, convenient, and eco-friendly transport options, this system addresses both the operational and security concerns associated with traditional ride-sharing services. The system is designed to provide students with a reliable platform for carpooling while maintaining privacy and enhancing security through multi-layered authentication methods. The paper outlines the system architecture, the integration of MFA mechanisms, the benefits of the system, and potential challenges.